On equivalence categories of microbundles - Matuzevičius, A. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Матузявичюс. Об эквивалентности категорий микропучковA. Matuzevičius. Apie mikroišsluoksniavimų kategorijų ekvivalentiškumą